ONLINE SHARING OF OFFLINE DO-IT-YOURSELF ACCESSIBILITY HACKING PRACTICES - Robinson, Jerry Lamont (AoIR Selected Papers of Internet Research, 2014)
Labels and their meanings are socially constructed and reinforced by the shared norms, structures, systems, and discourses of powerful social groups. This is especially true when it comes to hackers, disability, and technology. Although the term hacker originally referred to a highly skilled and "quirky" individual driven by a desire to achieve brilliant and innovative technological feats through machine manipulation [1] it has deviated from its original connotation due to the influence of the news media, government agencies, for-profit entities, and cyber crime victims wanting to justify greater spending on security and sanctions for hackers with malicious intentions [2]. In the same way that the voice of hackers with good intentions has been overpowered by discourses that opposed malicious hacking the needs and opinions of persons with disabilities are often ignored when institutions that provide products and services to them operate based on certain disability discourses. This study will add to our understanding of the politics of disability associated with rehabilitation technology, durable medical equipment (DME) assistive technology (AT), and technology funding agencies by exploring the DIY and hactivist-like activities that individuals with disabilities engage in offline and discuss online.